"Progress-Sharing" can mean Industrial Peace - Gagné, Jean-H. (Relations industrielles / Industrial Relations, 1952)
The article briefly reviews "'Progress-Sharing' can mean Industrial Peace," published in Reader's Digest, September, 1952, Canadian Edition, pages 81 to 85.